OBSERVATIONS ON THE LARVAE AND JUVENILES OF THE 'BHEKTI', LATES CALCAJUFER (BLOCH) FROM THE HOOGHLY-MATLAH ESTUARINE SYSTEM - Ghosh, Apurba (Indian Journal of Fisheries, 2011)
The cultivation of carnivorous fishes is a new trend in flsh culture practice throughouttheworld. Among such speciesLa^e; ca/car(/erXBIoch)is considered to be one of themost important in view of its excellent quality as a table fish. Investigations on the seedresources of these species is an essential pre-requisite for assessing the cultural possibilities.In the present communication an attempt is made to describe the characters oflarvae andjuvenilesof L.c